VAT treatment on foreign trade of services in Peru - Vásquez Nieva, Óscar (2021)
The VAT as a tax that affects the trade traffic of goods and services is limited to a certain territory where the taxable event must occur. In Peru, the VAT Law establishes that the Exportation of Services is not affected by this tax, but under certain conditions where the one that highlights are that the consumption of the service by the non-resident person must have place entirely abroad. As there is Export of Services, we can also talk about Import of Services or Use of Services provided by a non-resident person, but whose consumption or use occurs in our domestic territory regardless of the place of provision.